Efektivitas Game Edukasi dalam Meningkatkan Motivasi Belajar dan Kepuasan Siswa Indonesia - Wibowo, Tony; Apriyanti, Vivien Christy (Politeknik Harapan Bersama, 2024)
The lack of an effective and attractive learning system for students affects their low motivation in learning. Prior studies have shown that educational games that are appropriate to the context can improve students' performance, attitudes, motivation, and ability to think critically compared to non-game learning. This research aims to discover the effectiveness of educational games in increasing students’ learning motivation and satisfaction. Quantitative and qualitative approaches were conducted on 85 high school students from several High Schools in Batam, Indonesia. The quantitative data results were analyzed by SEM method, using SPSS and AMOS, while the qualitative data were analyzed using codification. Results proved that educational games positively affect students’ learning motivation and learning satisfaction. Nevertheless, the teacher’s explanation in class is still required for students to comprehend the learning materials properly. With these facts stated, schools should experiment with new learning method that combines educational game and traditional teaching method.